Sakralitas dan Komoditas Eksistensi Kafe di Sekitar Masjidil Haram - Nidaiyatul Fadhilah; Abdul Sattar (Kamaya: Jurnal Ilmu Agama, 2026)
Mecca has transformed into a cosmopolitan city, sparking a debate between the preservation of sacred values and the logic of global capitalism. The purpose of this study is to analyze the commercialization process of cafes around the Masjidil Haram and its impact on the sanctity of worship spaces. Data collection was conducted through participatory observation and in-depth interviews with 22 informants, using descriptive-analytical qualitative methods. The results show that the presence of cafes is a response to Saudi Vision 2030, transforming the area around the mosque into a hybrid space that combines worship and lifestyle. Theologically, the sanctity of the core of the Grand Mosque (al-sawabit) remains firmly intact, but the atmosphere in the outer zone (al-mutaghayyirat) has undergone a shift in meaning due to the normalization of the culture of “hanging out” and consumptive behavior. Cafes serve as transitional spaces that bridge physical needs with rituals, but they have the potential to distract from solemnity. The implications of this research emphasize the need for strict spatial and zoning policies to balance the comfort of modern facilities with spiritual integrity, ensuring that market dominance does not erode the essence of worship in the Holy Land. This study contributes to the study of the sociology of religion and sacred cities by conceptualizing cafes around the Grand Mosque as hybrid transitional spaces, sharpening our understanding of the sacred-profane relationship in the dimension of religious space.